Trade-off analysis of ecosystem service provision in nature networks - Vogdrup-Schmidt, Mathias; Strange, Niels; Olsen, Søren B.; Thorsen, Bo Jellesmark (Ecosystem services, 2017)
We propose a spatial multi-criteria decision analysis approach as a value-focused decision support tool for evaluating land use change decisions affecting multiple ecosystem services. In an empirical case study concerned with creating a robust and interconnected network of natural areas in a Danish municipality, we first conduct a biophysical and economic baseline mapping of ecosystem services. We then construct a spatially explicit multi-criteria decision analysis model which is utilized to identify candidate areas for inclusion in the network. We define a base scenario for future land use in the area, where all criteria have equal weight, and assess the outcome in terms of welfare economic benefits of ecosystem services and opportunity cost of reducing forest and agricultural production. As weights in multi-criteria analysis is innately a subjective task, we conduct a sensitivity analysis using four corner solution scenarios. The analyses illustrate the possible range of impacts and highlight the specific trade-offs between different ecosystem services. We argue that a multi-criteria decision analysis approach will help inform decision makers in a structured and informative way when considering future land use changes. •A biophysical and economic baseline mapping of ecosystem services.•Illustration of impacts and highlighting of trade-offs between ecosystem services.•Application of the multi-criteria decision analysis approach for land use changes.